Analysing Child Bullying Case from the Perspective of Media Political Economy and Islamic Communication in Ihya Ulum Al Din by Al Ghazali - Lailiya Nur Rokhman; Ihwan Huda Al Mujib (P3M Politeknik Negeri Jember, 2023)
The rise of child bullying cases has not escaped the media spotlight. News about cases found and their developments grab the attention of the public, especially bullying cases involving minors as perpetrators and victims. Children associated with cases that should have privacy and protection, in reality, become media and public consumption. Bullying cases no longer only focus on the case, but also the privacy of the perpetrators and victims. Responses from various communities have also been in the spotlight. Condemnation and blasphemy against the perpetrators then become their own form of bullying outside the case. One of the cases that caught the public's attention was the bullying case of Audrey, a junior high school student in Pontianak in 2019. The case even went viral and received public support through an online petition with the hashtag #justiceforaudrey. However, it was later discovered that the case was a fabrication made by Audrey after several years of the case going viral. The audience was then made guilty of blaming the alleged perpetrator without seeing the real truth first. Content about bullying cases is then no longer a bridge of information for the public, but also a business field and a place to get public attention. This research aims to dissect how cases of child bullying in the media from the perspective of media political economy and Islamic perspective communication.